Геохимические особенности городских ландшафтов Западной Сибири по данным изучения снежного покрова - Таловская А. В. Анна Валерьевна; Язиков Е. Г. Егор Григорьевич; Литау В. В. Виктория Викторовна; Филимоненко Е. А. Екатерина Анатольевна; Самохина Н. П. Наталья Павловна (2016, 2016)
Заглавие с экрана